Clinical and Microbiological Characteristics of Early Candidozyma auris Cases in a Tertiary Hospital in Istanbul, Türkiye: A Retrospective Case Series - Begüm Nalça Erdin; İrfan Aydın; Yüksel Akkaya; Meziyet Zeliha Gürlek Ustabaşı; Zeliha Alıcıkuş; Can Turan; İbrahim Halil Kılıç (Antibiotics, 2026)
Background: Candidozyma auris (C. auris) is an emerging multidrug-resistant yeast associated with healthcare-related transmission, difficult laboratory identification, antifungal resistance, and high mortality in critically ill patients. This study aimed to describe the clinical and microbiological characteristics of early institutional C. auris cases detected in a tertiary hospital in Istanbul, Türkiye. Methods: Adult patients hospitalized between January 2021 and December 2022 with C. auris isolation were retrospectively reviewed. Demographic data, underlying conditions, intensive care unit (ICU) exposure, invasive procedures, antimicrobial and antifungal use, culture sources, antifungal susceptibility testing (AFST) results, and clinical outcomes were evaluated. C. auris isolates were identified using VITEK MS v.3.2, and AFST was performed using C. auris isolates were identified using VITEK MS v.3.2, and AFST was performed using Sensititre YeastOne YO10 (Thermo Fisher Scientific, Waltham, MA, USA) panels. Results were interpreted according to CDC interim breakpoints. Multiple isolates from an individual patient were retained when they represented different specimen types or sampling events. Results: Thirty-three adult patients and 62 clinical isolates were included. The mean age was 67.8 years, and 20 patients (60.6%) were aged 65 years or older. Most patients had prior ICU admission (93.9%), urinary catheterization (97.0%), central venous catheterization (90.9%), mechanical ventilation (81.8%), and broad-spectrum antimicrobial exposure. Blood cultures represented the most frequent source of isolation (56.5%), followed by urine cultures (27.4%). Resistance rates were 98.4% for amphotericin B, 88.7% for fluconazole, 6.6% for micafungin, and 6.5% for caspofungin. Overall mortality was 72.7%. While mortality was numerically higher among patients aged 65 years or older and those requiring inotropic support, only the need for mechanical ventilation was statistically significantly associated with mortality. The cohort-level APACHE II-based expected mortality was 48.0%, whereas observed mortality was 72.7%; this comparison was descriptive and no formal calibration analysis was performed. Conclusions: Early institutional C. auris cases in this tertiary hospital occurred predominantly among elderly, critically ill patients with prolonged healthcare exposure, invasive devices, and extensive antimicrobial use. The findings support the need for early laboratory recognition, cautious interpretation of commercial AFST results, particularly given the propensity of Sensititre YeastOne to overestimate amphotericin B resistance, strengthened infection control practices, and multicenter studies incorporating molecular typing to clarify transmission dynamics and antifungal resistance patterns.